Answer:
![x=(d+c)/(a-b)](https://img.qammunity.org/2021/formulas/mathematics/college/4p8mytdmevwmzfhv87rgadnt1r7r5z0ahs.png)
Explanation:
The equation is:
a x - c = b x + d
so we subtract b x from both sides to group the terms that contain x on the left:
a x - b x - c = d
add c to both sides to isolate the terms in x on the left:
a x - b x = d + c
extract "x" as common factor on the left using distributive property backwards:
x (a - b) = d + c
divide both sides by the quantity (a - b) to isolate the "x":
x = (d + c) / (a - b)
or:
![x=(d+c)/(a-b)](https://img.qammunity.org/2021/formulas/mathematics/college/4p8mytdmevwmzfhv87rgadnt1r7r5z0ahs.png)